"I'm an Exhibitionist of Student Learning": Public presentations stimulate deeper learning. Issue 6 (2nd November 2018) - Pledger, Michelle Sadrena
Abstract : How we share student learning and encourage them to present their knowledge and discoveries to the broader community will have a significant impact on their self-confidence, their interest in learning more, and their ability to take leadership roles. We can tap into numerous innovative strategies and techniques to support students' presentation literacy and make a meaningful change to traditional instruction.